Droplet digital PCR for detection of mutations in high-grade serous ovarian cancer - Mahran, Randa (My University, 2020)
Ovarian cancer (OC) is one of the most fatal cancers that affect female reproductive system. It is frequently discovered at advanced stage therefore, the 5-year survival rate is typically low. High grade serous ovarian cancer (HGSOC) is the most aggressive and has the worst prognosis of all types of OC. It is characterized by copy number variation (CNV) and genetic instability. Circulating free DNA (cfDNA) is a potential non-invasive alternative to tissue biopsy that can be used to detect mutations for early screening and targeted treatment of HGSOC. Nevertheless, methods with higher sensitivity than real-time PCR (qPCR) are required for amplification and quantification of plasma cfDNA. Droplet digital PCR (ddPCR) is a very sensitive tool in rare mutations detection. It produces absolute quantification without the need for a standard curve. Additionally, it divides the sample into droplets where each droplet acts as an individual PCR reaction. This leads to high sensitivity in identification rare targets. The aim of this study was to evaluate the sensitivity of ddPCR in detection of TP53 mutation and three novel unpublished fusion genes in HGSOC. For TP53 detection, serial dilutions of Mutant (MT) in genomic DNA (gDNA) was tested to identify limit of detection (LOD). Next, different concentrations of plasma cfDNA (5, 10, 20 and 40 ng per reaction) from HGSOC patient were analyzed by both qPCR and the optimized ddPCR assay. DdPCR showed 1 % LOD and recorded 3720 MT copies/ μl when 40 ng cfDNA per reaction was used. On the other hand, qPCR LOD was 5 % and it failed to detect cfDNA. Based on these results, we suggest that ddPCR is more sensitive than qPCR in detection of rare mutations. As for the fusion genes, ddPCR was more challenging and required further optimization.
Keywords: Keywords:Ovarian cancer, ddPCR, mutations, fusion genes